Effects of switching frequency to series loaded series resonant circuit - Basri, Atikah Balqis; Zaidi, Nur Atif; Bopi, Nor Bazilah; Aboadla, Ezzidin Hassan; Khan, Sheroz; Habaebi, Mohamed Hadi (Asian Research Publishing Network (ARPN), 2016)
This paper analyses the effect of switching frequency on series loaded series resonant (SLSR) converter. SLSR converter is a well-known topology typically used for applications in kilowatt-range power supplies and can operate in either continuous or discontinuous conduction modes. The modes are determined according to the relationship between the switching frequency and resonant frequency. The analysis results in a set of equations with solutions presented graphically. The development of a SLSR converter is described along with the results of computer simulation. The output waveforms obtained for each switching frequency are compared.